Physicochemical and biological properties of new tricalcium silicate-based repair material doped with fluoride ions and zirconium oxide as radiopacifier - Campi, Lívia Bueno [UNESP]; Torres, Fernanda Ferrari Esteves [UNESP]; Rodrigues, Elisandra Márcia [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mário [UNESP] (Wiley, 2022)
This study evaluated the physicochemical and biological properties of novel reparative materials composed of pure tricalcium silicate (Ca3SiO5), Ca3SiO5 doped with fluoride ions (Ca3SiO5-F) and their association with ZrO2 (Ca3SiO5 + ZrO2, Ca3SiO5-F + ZrO2), in comparison with Biodentine (BIO). Setting time radiopacity, pH, solubility, and dimensional change were evaluated based on ISO 6876 Standard. Volumetric change and flow/filling were assessed by microcomputed tomography (micro-CT). Biological properties were evaluated by the MTT assay 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide), Neutral Red (NR), cell migration, alkaline phosphatase activity (ALP), and Alizarin Red Staining (ARS) assays. Statistical analysis was performed by ANOVA, Tukey, or Bonferroni tests (α =.05). Ca3SiO5-F + ZrO2 had higher radiopacity, shorter setting time, and lower solubility and volumetric loss than BIO (p <.05). Ca3SiO5-F + ZrO2 had flow and filling capacity similar to BIO (p >.05). All the cements evaluated had an alkaline pH. Ca3SiO5-F + ZrO2 demonstrated cell viability similar to negative control (p >.05), increase in ALP activity in 7 days, mineralized nodule production in 21 days and repair capacity according to cell migration. In conclusion, Ca3SiO5-F + ZrO2 had adequate setting time, radiopacity, solubility, and dimensional change. This material presented low volumetric change besides flow and filling capacity in micro-CT assessment. In addition, Ca3SiO5-F + ZrO2 was biocompatible and bioactive, suggesting its use as reparative material.
Keywords: biological properties; calcium silicate; chemical properties; fluoride; physical properties